Histomorphological and Immunohistochemical Analysis of Pleural Neoplasms - Sandhya Venkatachala; Swarna Shivakumar; Meganathan Prabhu; Ramya Padilu (Iranian Society of Pathology, 2018)
Background & objective:Primary pleural neoplasms are rare entities compared with the pleural involvement by metastatic carcinoma. The current study aimed at investigating the complete spectrum of pleural neoplasms and differentiating between them with the aid of immunohistochemistry (IHC). Methods: Consecutive pleural biopsy specimens positive for a neoplasm, both primary and metastatic, were included in the study. Diagnosis or a differential diagnosis was suggested on histopathology confirmed by a panel of IHC markers such ascytokeratin (AE1/AE3), epithelial membrane antigen (EMA), vimentin, calretinin, CD34, CD99, SMA, bcl2, S100, CK7,CK20,TTF1,GCDFP, HMB45, LCA, synaptophysin, chromogranin, and naspsin. Results: A total of 35 cases of pleural neoplasms included 15 (42.9%) primary pleural neoplasms and 20 (57.1%) metastatic carcinoma. Synovial sarcoma, malignant mesothelioma (MM), and solitary fibrous tumor (SFT) accounted for 14.2%, 11.4%, and 8.5% of metastatic cases, respectively. Epithelioid sarcoma (ES), neuroendocrine carcinoma, and inflammatory myofibroblastic tumor were less common, each contributing to 2.9% of pleural neoplasms. Among the 20 cases of metastatic carcinoma, 13 were from the lung and 7 from the breast. Lung neoplasms metastasizing to the pleura were adenocarcinoma (n=12) and atypical carcinoid (n=1). Conclusion: Analysis of histopathological pattern along with a panel of appropriate IHC markers distinguished the rare entities of pleural neoplasms essential to determine the prognosis and treatment modality.